2008
DOI: 10.1080/14992020802310879
|View full text |Cite
|
Sign up to set email alerts
|

Modification of otoacoustic emissions following ear-level exposure to MP3 player music

Abstract: The purpose of this study was to examine if a pre-determined exposure level and duration of MP3 player music would result in significant changes in cochlear function when measured with audiometric and physiological methods. Distortion-product otoacoustic emissions (DPOAEs), synchronized spontaneous otoacoustic emissions (SSOAEs), and hearing thresholds were measured in 20 normal-hearing adults before and after a 30-minute MP3 player music exposure. DPOAEs were acquired with 65/45 dB SPL primary tones (f(2)=0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
1
53
1
1
Order By: Relevance
“…7,[10][11][12] Although not documented in this study, these changes are probably temporary, as demonstrated by Bhagat and Davis, 7 but typically precede permanent changes in cochlear functioning and pure-tone hearing thresholds. 12 Since OAEs directly measure the responsiveness of the outer hair cells of the cochlea, which is the primary site of the lesion in noiseinduced hearing loss, these measures can identify changes in auditory functioning before conventional measures such as pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…7,[10][11][12] Although not documented in this study, these changes are probably temporary, as demonstrated by Bhagat and Davis, 7 but typically precede permanent changes in cochlear functioning and pure-tone hearing thresholds. 12 Since OAEs directly measure the responsiveness of the outer hair cells of the cochlea, which is the primary site of the lesion in noiseinduced hearing loss, these measures can identify changes in auditory functioning before conventional measures such as pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 88%
“…Post-match auditory tests indicated a significant average elevation in hearing thresholds at 2 000 Hz, and DPOAE amplitudes were significantly reduced at 1 266, 3 163 and 5 064 Hz. Although auditory changes probably reflect a temporary shift in hearing threshold and DPOAE amplitude, 5,7 they demonstrate that auditory physiology is affected by the sound exposure levels experienced at a football match where vuvuzelas are a major source of acoustic energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noise emitting devices such as personal music devices (PMDs) are now more compact and readily available (Danhauer et al 2009;Haines, Hodgetts, Ostevik, & Rieger, 2012;Hoover & Krishnamurti, 2010;Hodgetts, Szarko, & Rieger, 2009;Punch, Elfenbein, & James, 2011;Sulaiman, Husain, & Seluakumaran, 2014;Shah, Gopal, Reis, & Novak, 2009). PMDs are manufactured to produce output levels up to 110 dBA (Bhagat & Davis, 2008;, Kumar, Mathew, Alexander, & Kiran, 2009). Due to the availability, capacity and output levels of these devices research was conducted to assess possible effects on OHC functioning and hearing abilities.…”
Section: Introductionmentioning
confidence: 99%